An enquiry into the crippling gout affecting Pacific Islander and Māori men in Western Sydney. (6th October 2021) - Coleman, William; Spencer, David; Wong, Peter; Manolios, Nicholas
Abstract: Aim: Despite the effectiveness and availability of urate‐lowering therapies (ULT), we continue to see a number of advanced cases of tophaceous gout in the Pacific Islander and Māori population in Western Sydney. Although the high prevalence and increased severity of gout in this cohort has been well documented, there has been little qualitative research undertaken in Australia into the lived experience of this group of people. It is this gap in the research that our study aimed to address. Methods: Participants were recruited from the rheumatology clinics at Westmead and Blacktown Hospitals. Those eligible to participate were Pacific Islander and Māori patients with tophaceous gout currently living in the Western Sydney Local Health District (WSLHD). Data collection took the form of 10 semi‐structured interviews, which were subsequently transcribed verbatim. A thematic analysis of the data was then performed. Results: Thematic analysis identified 6 key themes: lack of understanding of the disease and its potential effects; missed opportunities for intervention and disjointed care; chronic reliance upon corticosteroids; trivialization of gout as a nuisance illness; the substantial financial impact of chronic illness; and the all‐consuming nature of severe gout. Conclusion: The human cost of severe tophaceous gout in this cohort is immense. All 10 participants exemplified the disease's devastating social effects. We propose 4 key recommendations: improved education regarding diagnosis and management; immediate prescription of ULT at first presentation; a lower threshold for out‐of‐hospital rheumatologist referral; and improved follow‐up through a nurse‐ and pharmacist‐led collaborative gout management program.